Komparasi Problem Based Learning dan Discovery Learning Berpendekatan Deep Learning Terhadap Peningkatan Keterampilan Berpikir Kritis Siswa pada Pembelajaran IPA: Systematic Literature Review - Ni Wayan Putri Febrianti Arintama; I Nyoman Suardana; Putri Sarini (STKIP HARAPAN BIMA, 2026)
This study aims to analyze and compare the effectiveness of Problem Based Learning and Discovery Learning models integrated with a Deep Learning approach in improving junior high school students’ critical thinking skills in science learning. This study employed a Systematic Literature Review (SLR) by collecting relevant scientific articles from Google Scholar. The procedure included formulating research questions, literature searching, determining inclusion and exclusion criteria, article selection, data extraction, and analysis. A total of 13 articles published between 2021 and 2026 were analyzed. Data were examined using a descriptive qualitative approach through comparison and synthesis of findings across studies. The results indicate that both PBL and Discovery Learning positively affect students’ critical thinking skills. PBL is more effective in enhancing problem-solving and collaborative discussion, while Discovery Learning better facilitates concept exploration and independent learning. The integration of the Deep Learning approach further strengthens conceptual understanding and supports the development of critical thinking skills.